2021
DOI: 10.1038/s41598-021-90204-8
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixation and denitrification activity differ between coral- and algae-dominated Red Sea reefs

Abstract: Coral reefs experience phase shifts from coral- to algae-dominated benthic communities, which could affect the interplay between processes introducing and removing bioavailable nitrogen. However, the magnitude of such processes, i.e., dinitrogen (N2) fixation and denitrification levels, and their responses to phase shifts remain unknown in coral reefs. We assessed both processes for the dominant species of six benthic categories (hard corals, soft corals, turf algae, coral rubble, biogenic rock, and reef sands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 156 publications
(210 reference statements)
0
11
0
Order By: Relevance
“…In contrast, even though octocorals constitute highly abundant members of benthic communities of coral reefs, their bacterial community dynamics under environmental stress remain largely unexplored ( 31 ). Octocorals were recently shown to exhibit some of the highest denitrification rates among Red Sea reef organisms and substrates ( 32 ), indicating a potential importance of this microbial functional trait to octocoral health and holobiont functioning. However, the (a)biotic drivers of denitrifier abundance and community composition in octocoral holobionts are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, even though octocorals constitute highly abundant members of benthic communities of coral reefs, their bacterial community dynamics under environmental stress remain largely unexplored ( 31 ). Octocorals were recently shown to exhibit some of the highest denitrification rates among Red Sea reef organisms and substrates ( 32 ), indicating a potential importance of this microbial functional trait to octocoral health and holobiont functioning. However, the (a)biotic drivers of denitrifier abundance and community composition in octocoral holobionts are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the sediment is considered to be another nitrogen source in some coral reefs. The flux rates of inorganic nitrogen from the sediment to the water column were about 0.046 nmol cm −2 h −1 [ 53 ]. Taken together, nitrogen supplement associated with coral community may be the key environmental factor that impacts the water bacterial and carbon-fixation bacterial community.…”
Section: Discussionmentioning
confidence: 99%
“…Global and local environmental change threaten to destabilize the functioning of coral holobionts and the reefs they support [10][11][12][13]. Importantly, diazotrophs in reef-building corals are susceptible to changing environmental conditions [3,8,9,[13][14][15][16][17][18]. Previous studies have reported that coral bleaching, the stressinduced breakdown of stable holobiont functioning, not only results in the loss of Symbiodiniaceae but also coincides with the opportunistic proliferation of diazotrophs [13,19,20].…”
Section: Introductionmentioning
confidence: 99%